Exploring Past, Present and Future of Orthotics and Prosthetics in Pakistan - Liaqat, Maria; Shaukat, Saima; Babur, Muhammad Naveed (Jurnal Medis Islam Internasional, 2021)
This is a qualitative study to explore the perception of Orthotists and Prosthetists regarding past, present and future of their profession. The Qualitative research approach using individual interviews. Data was collected from professionals of some private and some government sector in Rawalpindi, Peshawar and Lahore during April 2019 to July 2019. The sample size was 12. A demographic questionnaire and standarized instrument from Nvivo was filled satisfying the inclusion criteria. A comprehensive audio-videography have been developed, recorded, transcripted and documented. Data was transcribed and thematic analysis along with characteristics was drawn manually. Data verification was done with the help of coders. After the extraction of data followings results are emerged.  General category themes are trainings and seminars, opportunities, government setup, lack of coherence among professionals, uniform curriculum, and establishment of council, effects of earthquake, German contribution and techniques/technology. Barriers are identified at the level are lack of awareness/ acknowledgement, low job opportunities, no proper workshops, poor referral system, limited resources and old technologies. It is concluded that the field of orthotics and prosthetics in Pakistan need attention in the following categories i.e. trainings and seminars, job opportunities, uniform curriculum, unity among professionals, establishment of council, acknowledgment at government level and awareness among other health professionals.